The oxidative kinetics of uranium at different stages. (September 2022) - Wang, Shuaipeng; Li, Haibo; Li, Gan; Tang, Tao; Gu, Yuejiao; Hu, Yin; Chen, Xianglin; Wang, Yun; Lv, Junbo; Luo, Wenhua
Abstract: The oxidative kinetics of uranium at different stages (parabolic stage, transition stage, linear stage and decline stage) was researched by the comprehensive methods, including the reflectance spectroscopy and the oxygen-consumption method. The oxidative kinetics models were established and the mechanism behind the kinetics laws was also analyzed. Especially, the kinetics of transition stage, which connects the initial parabolic stage and the linear stage and was rarely reported, was obtained quantitatively. The kinetics models covering the different stages of oxidation could support the prediction of the corrosion degree of uranium in the long-period storage. Highlights: The oxidation kinetics of uranium was researched by the reflectance spectroscopy and the oxygen-consumption method. The kinetics models of uranium at different stage were established and the mechanism was analyzed. Especially, the kinetics of transition stage, which was rarely reported, was proposed quantitatively. The kinetics models could support the corrosion prediction of uranium in the long-period storage.